(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Manitskaya Ekaterina Olegovna The article is devoted to the existence of myths in modern texts. As an example it was selected a series of novels about Merlin and King Arthur by British writer Mary Stewart, written in the twentieth century. In this novels, the author resorts to key mythologem of Arthurian myth, such as the sword Excalibur, the Holy Grail and the Round Table, turning them into symbols of pseudo-realities. Due to this the Sword and the Grail becom a Roman artifacts that Merlin is to give Arthur as real symbols of the power of predestination. Excalibur in this case becomes a symbol of the reunification of the country on both the political and the religious aspect. Grail turns into an object of false pursuit, because the role he must fulfill is given to Arthur. Roundtable loses its symbolic meaning: the author finds a historical explanation for this mythologeme and assigns a place in the Round Knights of Arthur’s house, which is really able to accommodate more than a hundred people at once. Thus, each of the myths in the text is not just a myth intended to make the myth-source recognizable, but also performs new functions ascribed by the author. Key words: Arthur legends, mythologems, neomythologism, Mary Stewart.